ISOLATION AND IDENTIFICATION OF Î²-SITOSTEROL AND STIGMASTEROL MIXTURE FROM ROOT BARK OF SLATRI (Calophyllum soulattri Burm. f) - Saputra, Doni Eko; Handayani, Nestri; Wartono, Muhammad Widyo (Alchemy Jurnal Penelitian Kimia, 2014)
Chemical isolation and identification of root bark of Calophyllum soulattri Burm. f. have been conducted. Isolation was conducted by maceration with ethyl acetate as solvent. Ethyl acetate extract was separated and purified by vacuum liquid chromatography and flash chromatography which was guided by thin layer chromatography to obtain yellowish white solid. Isolated compounds were determined by spectroscopy methods such as UV, FTIR, 1H NMR, 13C NMR, DEPT, HSQC, HMBC and were compared to the references. Based on the analysis result itâs known that the compounds are the mixture of Î²-sitosterol and stigmasterol.